2019
DOI: 10.1002/acp.3531
|View full text |Cite
|
Sign up to set email alerts
|

An experimental examination of the effects of alcohol consumption and exposure to misleading postevent information on remembering a hypothetical rape scenario

Abstract: Summary We experimentally examined the effects of alcohol consumption and exposure to misleading postevent information on memory for a hypothetical interactive rape scenario. We used a 2 beverage (alcohol vs. tonic water) × 2 expectancy (told alcohol vs. told tonic) factorial design. Participants (N = 80) were randomly assigned to conditions. They consumed alcohol (mean blood alcohol content = 0.06%) or tonic water before engaging in the scenario. Alcohol expectancy was controlled by telling participants they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 101 publications
2
40
0
Order By: Relevance
“…Both Altman et al () and Gawrylowicz et al () reported results in line with the adapted AMT. However, the findings of Flowe et al () did not support the adapted AMT and suggested that intoxicated individuals were able to process both salient and peripheral cues as well as individuals who were not intoxicated.…”
Section: Four Mechanismsmentioning
confidence: 92%
See 4 more Smart Citations
“…Both Altman et al () and Gawrylowicz et al () reported results in line with the adapted AMT. However, the findings of Flowe et al () did not support the adapted AMT and suggested that intoxicated individuals were able to process both salient and peripheral cues as well as individuals who were not intoxicated.…”
Section: Four Mechanismsmentioning
confidence: 92%
“…The reverse placebo group drank alcohol but were not expecting the detrimental effects associated with intoxication and, hence, were unaware that they needed to take measures to preserve their memory. Flowe et al () found mixed support. Although they found that participants who expected to drink alcohol did not recall the event more accurately, they found increased accuracy discrimination on the recognition test for these participants.…”
Section: Four Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations